Endoscopic cerebrospinal fluid leak repair combined with thecoperitoneal shunting for spontaneous cerebrospinal fluid rhinorrhea: MERF experience - Gajapathy, Sowmya; Kumar, Raghunandhan Sampath; Natarajan, Kiran; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Spontaneous cerebrospinal fluid (CSF) rhinorrhoea is encountered as a diagnosis of exclusion in clinical practice once all other aetiologies have been meticulously ruled out and can mostly present from preformed pathways due to benign intracranial hypertension (BIH) over time. Such leaks need to be clearly located for planning appropriate repair along with adequate control of CSF pressure to avoid recurrence. Thus, the aim of our study was to review the efficacy and outcomes of a combined endoscopic multilayered repair along with simultaneous theco-peritoneal shunting (TPS) for patients with spontaneous CSF rhinorrhoea in the background of BIH. Methods: Retrospective observational study analyzing the clinical presentations, surgical techniques and the immediate / long term outcomes of this combined approach. Results: The 46 patients who had endoscopic CSF repair with TPS done between 2008-2019 were reviewed. The mean opening CSF pressure in these cases were >25 cm H2O. The commonest site of leak was from cribriform plate followed by fovea ethmoidalis. Multilayered closure was done with autologous grafts along with TPS simultaneously. The 92% were successful, 6% had shunt problems needing revision shunts and 2% also needed revision endoscopic repair. Conclusions: Overall outcomes shows that the combined approach was safe and effective in arresting the CSF leak in 98% patients. Therefore, the rationale for a combined approach for the management of spontaneous CSF leaks in the background of BIH stands proven based on our Institutional experience.